2021
DOI: 10.7554/elife.67535
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of hypothalamic oxytocin neurons suppresses colorectal cancer progression in mice

Abstract: Emerging evidence suggests that the nervous system is involved in tumor development in the periphery, however, the role of central nervous system remains largely unknown. Here, by combining genetic, chemogenetic, pharmacological and electrophysiological approaches, we show that hypothalamic oxytocin (Oxt)-producing neurons modulate colitis-associated cancer (CAC) progression in mice. Depletion or activation of Oxt neurons could augment or suppress CAC progression. Importantly, brain treatment with celastrol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…As shown in rats, activation of this pathway can increase insulin levels (Bjorkstrand et al, 1996), reduce heart rate and cardiac contractility (Houshmand et al, 2015), suppress food and water intake of the digestive system (Niimi et al, 2001), slow gastric emptying (Tolentino et al, 2021) and regulate hepatic metabolic activity (Dos . Recently, it is also reported that activation of brain OT neurons inhibits colitis-associated cancer progression in association of suppression of sympathetic neuronal activity in the celiac-superior mesenteric ganglion as shown in mice (Pan et al, 2021). Thus, OT can modulate visceral activities by increasing parasympathetic nervous activity although the parasympathetic outflow function of endogenous OT remains to be studied.…”
Section: Effects On Autonomic Nervous Systemmentioning
confidence: 99%
“…As shown in rats, activation of this pathway can increase insulin levels (Bjorkstrand et al, 1996), reduce heart rate and cardiac contractility (Houshmand et al, 2015), suppress food and water intake of the digestive system (Niimi et al, 2001), slow gastric emptying (Tolentino et al, 2021) and regulate hepatic metabolic activity (Dos . Recently, it is also reported that activation of brain OT neurons inhibits colitis-associated cancer progression in association of suppression of sympathetic neuronal activity in the celiac-superior mesenteric ganglion as shown in mice (Pan et al, 2021). Thus, OT can modulate visceral activities by increasing parasympathetic nervous activity although the parasympathetic outflow function of endogenous OT remains to be studied.…”
Section: Effects On Autonomic Nervous Systemmentioning
confidence: 99%
“…OXT inhibited ovarian cancer metastasis by suppressing the expression of MMP-2 and VEGF ( 73 ). Interestingly, stimulation of hypothalamic OXT neurons inhibited the progression of colorectal cancer in mice ( 74 ). Thus OXT may be a new strategy for the treatment of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanisms underlying the effects of psychological stress on malignant disease, multiomics studies, such as cytomics, genomics, metabolomics, proteomics, and bioinformatics analytical approaches, can be applied to explore the key mediators of psychological distress and eustress in malignant diseases and to develop relevant targeted therapies or to find prognostic biomarkers. In addition to the SNS and HPA axes, other molecules associated with stress coping may also have effects on malignant tumors, including dopamine, serotonin, and oxytocin ( 89 , 90 , 128 ). And the impact of these mediators on malignancies could be of interest in future studies.…”
Section: Summary and Future Considerationsmentioning
confidence: 99%